The Influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Costs to Operating Income (BOPO) on Liquidity as Measured by Loan to Deposit Ratio at HSBC Bank - Elwardi Hasibuan; Dian Purnama Sari; Hablil Ikhwana (ProBisnis : Jurnal Manajemen, 2020)
The purpose of this research is to analyze and test the effect of CAR, NPL, BOPO on HSBC Bank's LDR. This type of research is explanatory research. The sample used in this study is HSBC Bank which published its financial reports in the 2006-2013 period. Data collection techniques are library research and field research. This study used descriptive analysis, classical assumption test and multiple linear regression for data analysis with the help of the Eviews 8 program. From the analysis test results it is known that the CAR, BOPO and NPL ratios have no effect on the LDR ratio during the 2006-2013 period.